Critical Discourse Analysis on Name Shifting Practice among Millennial Muslims in the Indonesian Context - Farah, Rafika Rabba; Wiraatmaja, Triastama; Sumarsono, Puji (KARSA Journal of Social and Islamic Culture, 2022)
Name-giving is not merely a compilation of words to meet official record registration, yet the idea behind this has some socio-cultural values. Indonesian Muslim names have now experienced some changing from the past. This research aims at analyzing the discourse of millennial Muslim names in Indonesia. NVivo 12 Plus was used to analyze the nodes data of three categories—Pure Indonesian, Pure Arabic, and Mixing across its case—parents and children. Another analysis used was word frequency to picture the frequent word clouds used in parents' and children's naming practices. Results show a shift in Indonesian millennial Muslims' naming practice, as the Pure Arabic and Mixing categories have upward trends compared to the Pure Indonesian variety. This present research has shed a light that Indonesian Millennial Muslim parents want to pertain their children's identity as Muslims and want their children to be part of the global world.